State of the art of each partner country on experiences in game-based learning and gamification - Silva, Bento Duarte da (2018)
This article, written under the scope of the Erasmus+ project «Games2Learn & Gamification2Engage», sought to identify the teachers' perceptions from the three countries (Portugal, Italy and Poland) involved in the project on GBL and Gamification. The goals were to find out what these teachers know about GBL and Gamification, and its use as pedagogical innovation scenarios. To achieve these goals, a survey was distributed to 15 teachers participating in the training organised under the project.